1997
DOI: 10.1364/josab.14.000076
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded second-order effects in N-(4-nitrophenyl)-L-prolinol, in a molecular single crystal

Abstract: An investigation of cascaded second-order optical effects resulting in effective third-order interactions, temporal and spatial self-action, are presented for N-(4-nitrophenyl)-L-prolinol (NPP) a molecular single crystal with one of the largest phase-matchable second-order nonlinear coefficients known in the visible and near-infrared portions of the spectrum. We emphasize the effects of temporal and spatial walk-off in the nonlinear-optical propagation in NPP and discuss their consequences for cascaded second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, longer interaction lengths and higher nonlinearities are required. As mentioned in Section 2.1.2.1, high nonlinearities can be achieved with organic materials, such as DAST, which is phase matchable for type I and type II conditions, and N-(4-nitrophenyl)-L-prolinol (NPP) [67,68]. Those materials are often used for terahertz generation and mode-locking.…”
Section: Cascaded Kerr E Ect Type IImentioning
confidence: 99%
“…Therefore, longer interaction lengths and higher nonlinearities are required. As mentioned in Section 2.1.2.1, high nonlinearities can be achieved with organic materials, such as DAST, which is phase matchable for type I and type II conditions, and N-(4-nitrophenyl)-L-prolinol (NPP) [67,68]. Those materials are often used for terahertz generation and mode-locking.…”
Section: Cascaded Kerr E Ect Type IImentioning
confidence: 99%
“…In the experiment, they clearly demonstrated large nonlinear phase shifts. This experiment paved the way to the experimental investigation in other nonlinear quadratic materials: ␤-barium borate by means of self-diffraction, 12 potassium niobate, 13 potassium dihydrogen phosphate, 14 organic N-(4-nitrophenyl-Lprolinol, 15 and periodically poled lithium niobate. 16 A theoretical description of nonlinear phase distortions in (2) materials was made by numerical integration of the nonlinear differential equations that describe the propa-gation of plane waves.…”
Section: Introductionmentioning
confidence: 99%
“…Design and synthesis of efficient organic nonlinear optical (NLO) materials are very important due to their potential applications in the fields of telecommunication, optical data storage and optical information processing. Nitrophenyl derivatives are NLO materials1–3 and have been used for a very efficient frequency‐conversion process based on cascading 4. Zyss et al 5 reported the NLO properties of N ‐(4‐nitrophenyl)‐ L ‐prolinol.…”
Section: Introductionmentioning
confidence: 99%